Mitochondrial DNA-based genetic variation of Anopheles aquasalis, a malaria vector in Venezuela - Herrera, Flor; Ruiz, Johanny; Pacheco, César (Journal of Current Health Sciences, 2025)
The Plasmodium parasites are responsible for the severe public health malaria disease happening in Venezuela. In the year 2022, the estimated malaria cases in Venezuela were 178.000 with 190 deaths. An. aquasalis is the main malaria vector in the northern coastal part of Venezuela, distributed along the entire coast, from the Guajira Peninsula in the Zulia State to the Delta Amacuro State. This study aimed to investigate the genetic diversity and population structure of the vector An. aquasalis from coastal regions of Venezuela through single strand conformation polymorphism markers of the mitochondrial NADH dehydrogenase (ND5) gene. Adult mosquitoes were collected between November 2017 and December 2018. A 450-bp region of the ND5 gene was amplified by the polymerase chain reaction and tested for variation using SSCP among 358 An. aquasalis from seven localities near the coast of the States of Zulia, Falcón, Carabobo, Aragua, Miranda, Sucre, and Delta Amacuro of Venezuela separated by up to 1960 km. This study revealed that the populations of An. aquasalis in Venezuela are highly polymorphic, with high genetic diversity among 48 haplotypes detected throughout Venezuela and sorted into four clades. In addition, a significant An. aquasalis genetic population structure was found, apparently in response to geographical barriers and ecological differences.